2008
DOI: 10.1113/jphysiol.2008.153916
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of resistance and endurance exercise in the fed state on signalling molecule phosphorylation and protein synthesis in human muscle

Abstract: Resistance (RE) and endurance (EE) exercise stimulate mixed skeletal muscle protein synthesis. The phenotypes induced by RE (myofibrillar protein accretion) and EE (mitochondrial expansion) training must result from differential stimulation of myofibrillar and mitochondrial protein synthesis. We measured the synthetic rates of myofibrillar and mitochondrial proteins and the activation of signalling proteins (Akt-mTOR-p70S6K) at rest and after an acute bout of RE or EE in the untrained state and after 10 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
520
12
19

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(588 citation statements)
references
References 73 publications
37
520
12
19
Order By: Relevance
“…In the present study, we showed attenuated phosphorylation of p70S6K and rpS6 with chronic resistance exercise-like electrical stimulation inducing a maximal isometric contraction. Although few studies examined change in phosphorylation status with training in animal study, a previous study in humans examined the anabolic signaling response to a bout of resistance exercise before and after 10 wk of resistance training (41). This study demonstrated that the duration of elevated Akt, p70S6K, and GSK3-␤ phosphorylation was reduced in trained participants compared with untrained participants, and rpS6 phosphorylation, which was elevated in the untrained state, was not increased after the 10-wk training period (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we showed attenuated phosphorylation of p70S6K and rpS6 with chronic resistance exercise-like electrical stimulation inducing a maximal isometric contraction. Although few studies examined change in phosphorylation status with training in animal study, a previous study in humans examined the anabolic signaling response to a bout of resistance exercise before and after 10 wk of resistance training (41). This study demonstrated that the duration of elevated Akt, p70S6K, and GSK3-␤ phosphorylation was reduced in trained participants compared with untrained participants, and rpS6 phosphorylation, which was elevated in the untrained state, was not increased after the 10-wk training period (41).…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies examined change in phosphorylation status with training in animal study, a previous study in humans examined the anabolic signaling response to a bout of resistance exercise before and after 10 wk of resistance training (41). This study demonstrated that the duration of elevated Akt, p70S6K, and GSK3-␤ phosphorylation was reduced in trained participants compared with untrained participants, and rpS6 phosphorylation, which was elevated in the untrained state, was not increased after the 10-wk training period (41). Furthermore, another human study reported that the phosphorylation of p70S6K and rpS6 did not increase after a session of resistance exercise in highly resistance-trained subjects (power lifters), whereas increases in these phosphoproteins were observed in untrained subjects (8).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of mTOR signaling pathways, however, appears to be small or brief after cycle exercise compared to resistance exercise. For example, S6K1 phosphorylation has been shown to increase above basal levels immediately after both cycle and resistance exercise 46) ; but, after 4 h, the elevation of S6K1 phosphorylation remained only after the resistance exercise 46) . Furthermore, one study showed that myofibrillar protein synthesis was stimulated over the 4 h period following resistance exercise, but not after cycle exercise 46) .…”
Section: Muscle Hypertrophy With Endurance Trainingmentioning
confidence: 99%
“…For example, S6K1 phosphorylation has been shown to increase above basal levels immediately after both cycle and resistance exercise 46) ; but, after 4 h, the elevation of S6K1 phosphorylation remained only after the resistance exercise 46) . Furthermore, one study showed that myofibrillar protein synthesis was stimulated over the 4 h period following resistance exercise, but not after cycle exercise 46) . These demerits of cycling exercise, resulting from relatively small mechanical stresses, may account for the small effect size and many training sessions required for muscle hypertrophy compared to resistance training.…”
Section: Muscle Hypertrophy With Endurance Trainingmentioning
confidence: 99%
“…Resistance exercise increases the synthesis of muscle myofibrillar proteins (14) . Sufficient amino acids must be consumed to support increased synthesis.…”
Section: Muscle Hypertrophymentioning
confidence: 99%